“Teledentistry” using a mobile app (Telesmile) to improve oral health among the visually impaired and hearing-impaired populations in Saudi Arabia: a randomized controlled study - Hytham N. Fageeh; Manawar A. Mansoor; Hammam I. Fageeh; Hina N. Abdul; Hamza Khan; Abdulrahman Akkam; Idris Muhaddili; Sultan Korairi; Ashok Kumar Bhati (Frontiers in Oral Health)
ObjectiveTo assess the efficacy of a “teledentistry” method using a mobile app (Telesmile) in enhancing knowledge of oral health conditions and oral hygiene practices among the blind and deaf populations in Jazan Province in Saudi Arabia.MethodsA randomized parallel design controlled study was conducted among 50 blind and 50 deaf subjects between the ages of 12–18 years, randomly chosen from blind and deaf schools. The participants were selected based on the inclusion and exclusion criteria. An innovative teledentistry platform named Telesmile, a mobile application for the Apple iOS App Store and Google Play Store, was developed. Multimedia Arabic dental sign language oral hygiene instructional videos were created and uploaded in the Telesmile mobile application under the deaf category. Similarly, oral hygiene instructions were audio recorded by experts and uploaded under the blind category in the Telesmile mobile application. Group I of the blind (n = 25) and deaf participants (n = 25) received regular oral hygiene instructions while Group II of the blind (n = 25) and deaf (n = 25) participants received the Telesmile mobile application intervention. The knowledge of the participants pertaining to oral health and oral hygiene practices was evaluated using a close-ended questionnaire comprising 14 questions at the initial visit (T0). Training sessions were conducted for all participants and the Telesmile mobile application was distributed among the participants in Group II. After 4 weeks (T1), the knowledge of the participants regarding oral health and hygiene practice was re-evaluated and compared between each group.ResultsThe chi-square test revealed that the marginal mean of the knowledge of the blind and deaf participants pertaining to oral health and oral hygiene practices was very poor at their initial visit (T0) and it significantly increased (p < 0.001) after 4 weeks (T1) of using the Telesmile mobile application.ConclusionThe Telesmile mobile application can significantly enhance oral hygiene knowledge among blind and deaf people. The audio technique was an effective tool to deliver oral health education which could result in improving the oral health status of blind participants. The video demonstrations were also effective in enhancing the oral health and oral hygiene knowledge of deaf individuals.